Деякі правові аспекти запровадження інтернету речей - Колодін, Денис Олексійович; Kolodin, Denis (ВД "Гельветика", 2019)
У статті досліджуються суспільні відносини, що виникають з приводу використання «інтернету речей», на предмет необхідності їх правового регулювання. Автор дає загальну характеристику шляхів використання «інтернету речей» у різних сферах суспільного життя сучасної людини. Також виокремлюються найбільш пріоритетні сфери, пов’язані з функціонуванням «інтернету речей», які потребують нагального правового регулювання, а саме: захист персональних даних і питання використання інформації, зібраної інтернетом речей, як доказів під час розкриття злочинів. Зроблено висновок про необхідність створення спеціальних правових норм для регулювання відповідної сфери суспільних відносин як на законодавчому, так і на міжнародному рівнях.

The article deals with the social relations that arise in connection with the use of the Internet of Things for the necessity of their legal regulation. The author gives a general description of the ways of using the “Internet of Things” in various spheres of the social life of the modern person. Today, the Internet of things has already spread in many spheres of life, in particular, in the following: 1) Housing; 2) Medicine; 3) Sports; 4) Industry; 5) Fun. Also, the article highlights the most priority areas related to the functioning of the “Internet of Things”, which require urgent legal regulation, namely: the protection of personal data and the use of information collected by the Internet of things as evidence in the disclosure of crimes. The most urgent problem that needs legal regulation is the problem of confidentiality of Internet users' data at the moment. Large volumes of private information are available to companies producing goods that have access to the Internet. In particular, information about the physical health of millions of people using fitness trackers can be used by third parties for their own purposes. And it's not just about the distance a person has during the day or the number of calories burned. It should be noted that the ordering of relations regarding the use of “IoT” are not limited to the subject of legal regulation of civil law. Obviously, some aspects of the use of things with access to the Internet will be criminal and legal. The question of collecting and using evidence obtained through Internet-based content requires legal regulation. Otherwise, the evidence obtained with the help of a smartwatch helped uncover the killings, which led to a loud international scandal and the confrontation of entire countries. Conclusions are made on the necessity of creating special legal norms for regulation of the relevant sphere of public relations both at the legislative and international levels.
Колодін Д. О. Деякі правові аспекти запровадження інтернету речей / Д. О. Колодін // Часопис цивілістики : наук.-практ. журн. / редкол.: С. В. Ківалов (голов. ред.), Є. О. Харитонов (заст. голов. ред.), К. Г. Некіт (відп. секр.) [та ін.]. – Одеса : Гельветика, 2019. – Вип. 33. – С. 83-86.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; інтернет речей; правове регулювання; штучний інтелект; захист персональних даних; розкриття злочинів; Internet of things; legal regulation; artificial intelligence; protection of personal data; disclosure of a crime